2018
DOI: 10.3389/fimmu.2018.01289
|View full text |Cite
|
Sign up to set email alerts
|

IRE1α Implications in Endoplasmic Reticulum Stress-Mediated Development and Pathogenesis of Autoimmune Diseases

Abstract: Inositol-requiring transmembrane kinase/endoribonuclease 1α (IRE1α) is the most prominent and evolutionarily conserved endoplasmic reticulum (ER) membrane protein. This transduces the signal of misfolded protein accumulation in the ER, named as ER stress, to the nucleus as “unfolded protein response (UPR).” The ER stress-mediated IRE1α signaling pathway arbitrates the yin and yang of cell life. IRE1α has been implicated in several physiological as well as pathological conditions, including immune disorders. Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 337 publications
(402 reference statements)
3
70
0
Order By: Relevance
“…Under ER stress, IRE1α is involved in virus-mediated apoptosis (Huang et al, 2016). The IRE1α activates the nuclear factor-kappa B signalling pathway (Lencer, DeLuca, Grey, & Cho, 2015) and the expression of proinflammatory cytokines in immune cells (Junjappa, Patil, Bhattarai, Kim, & Chae, 2018). A previous study has demonstrated that the RIDD pathway promotes inflammation and apoptosis via the NLRP3 inflammasome (Lerner et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Under ER stress, IRE1α is involved in virus-mediated apoptosis (Huang et al, 2016). The IRE1α activates the nuclear factor-kappa B signalling pathway (Lencer, DeLuca, Grey, & Cho, 2015) and the expression of proinflammatory cytokines in immune cells (Junjappa, Patil, Bhattarai, Kim, & Chae, 2018). A previous study has demonstrated that the RIDD pathway promotes inflammation and apoptosis via the NLRP3 inflammasome (Lerner et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Whether these abnormal proteins induce immunogenic effects still needed to be elucidated systematically. The roles of ER stress and its signaling pathways in immune responses have been comprehensively reviewed recently 35, 36.…”
Section: The Immunosuppressive Activity Of Xbp1 In Cancer Cellsmentioning
confidence: 99%
“…When ER stress occurs, the transcription factor CHOP can cause the release of Cyt C and apoptosis-inducing factors (AIFs), which results in cellular apoptosis [ 18 20 ]. Moreover, the highly conserved ER membrane protein IRE1 α can be phosphorylated and induce cell apoptosis by activating an alternative pathway through TRAF2- and apoptosis signal-regulating kinase 1 (ASK1)-mediated signal transduction [ 21 ]. Pre-treatment with PhG-RE reduced the mRNA expression of GRP78, CHOP, and Caspase-12 during ER stress in H 2 O 2 -induced cells, as well as the TG-induced mRNA expression of GRP78, JNK, and Caspase-12.…”
Section: Discussionmentioning
confidence: 99%